Consumer IoT and its under‐regulation: Findings from an Australian study. Issue 1 (21st February 2022) - Harkin, Diarmaid; Mann, Monique; Warren, Ian
Abstract: The expansive growth of consumer internet of things (IoT) has created a range of concerns around privacy, security, and their broader societal impacts. This article reports on findings from interviews with 32 key stakeholders from the fields of information security, policy and regulation, the IoT industry, consumer and privacy law, and academia in Australia. It details a broad variety of issues and concerns that go beyond the well‐recognised issue of privacy or the technical standards of information security, to encompass a wider set of issues regarding the implications for vulnerable communities, the environment and industrial standards of IoT production. Most key stakeholders expressed the view that more robust regulation is required in Australia, but no clear regulatory priority or strategy was identified by our sample. The implications of these findings for further regulation of consumer IoT and future regulatory strategies are considered.